Human Resources Training For Organ Procurement in Transplantations: Distance Learning (Research, Society and Development, 2019)
Transplantation is the only treatment for some diseases, and in many cases, it represents the hope of living for patients in waiting lists. In Brazil, the percentage of families that refuse to donate their relatives’ organs is still high. Therefore, health professionals prepared to work with those families during the donation process are required. The goal of this study was to develop and organize a distance learning course about organ donation and transplantation. It aimed at qualifying and preparing doctors and nurses in Emergency and Intensive Care Units in the State of Rio Grande do Sul. The course’s activities had a blended learning approach, and 30 professionals participated in it. Results show that the course benefited professionals from different regions in the State. It prepared them to work in the organ donation and transplantation process. This was deemed relevant because participants were able to reflect on their donation and transplantation actions and improve them. The course allowed training of professionals who could not travel to large urban centers. The distance learning model was developed by specialists and offered updated material, which made taking the course easier and was a positive aspect according to all participants.